Intercultural Communication Harmony of Bugis Migrants in Building Social Networks within Palm Oil Plantation Areas - Sitti Murni Kaddi; M. Junaidi; Muh. Zainuddin Badollahi; Hilda Anjarsari; Roman Rezki Utama; Wahyu Aprijal Siruah; Jimmy Wong Batewa; Najwa Zahiyah Amanda (Jurnal Bisnis dan Komunikasi Digital, 2025)
This study examines the forms of intercultural communication harmony practiced by Bugis migrants in building social networks within the oil palm plantation areas of Baras District, Pasangkayu Regency. The research is significant because Bugis migrants, known for their long-standing migratory tradition (sompe’) and cultural values of siri’ na pacce, contribute to multicultural integration in plantation-based communities. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and focus group discussions, and analyzed with the Miles and Huberman model comprising data reduction, data display, and conclusion drawing. The findings indicate that intercultural harmony is expressed through openness in social interactions, solidarity in community life, tolerance among religious groups, interethnic marriages, inclusive economic cooperation in plantation work, and the preservation of cultural identity alongside adaptation. These practices strengthen social networks across ethnic boundaries and minimize potential conflicts in a multicultural environment. The study underscores the importance of intercultural communication as a foundation for social cohesion in plural societies. It also provides practical insights for policymakers and community leaders in managing diversity within plantation contexts. The originality of this research lies in its focus on the intercultural communication harmony of Bugis migrants in plantation-based communities, a perspective that has received limited scholarly attention.